Knotting of a nasogastric feeding tube in a child with head injury: A case report and review of literature - Nasiru J Ismail; Gyang Markus Bot; Ismail Hassan; Danaan J Shilong; Joseph O Obande; Salamat Ahuoiza Aliu; Ezekiel D Dung; Bello B Shehu (Wolters Kluwer Medknow Publications, 2014)
Nasogastric intubation is one of the most common routine nonoperative procedures available for the hospital care of patients. The insertion and removal of this tube is associated with many complications. The complications include trauma, nasal septal abscess and inadvertent entry into the cranial cavity and trachea, ulceration, bleeding from varices and perforation. Knotting of the nasogastric tube is one of the very rare complications of nasogastric intubation particularly in children. To the best of our knowledge there are very few reported cases in children. The technique used in the patient was the application of a steady tug which allows the lower oesophageal sphincter to open, therefore enabling the removal of the nasogastric tube. The possible predispositions to knotting of a nasogastric tube include small bore tubes, excess tube length and gastric surgery. We postulate that reduced gastric tone is another possible predisposing factor with head injury being the most likely reason in the index patient. We also challenge the fact that the small sized stomach is a risk factor for knotting of a feeding tube if the functional status and tone are normal, because of the rarity in children.